Atomic defects and physical-chemical properties of PbTe-InTe solid solutions - Freik, D.M.; Boychuk, V.I.; Mezhylovsjka, L.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Crystal-quasichemical equations of probable mechanisms inherent to formation of solid solutions based on lead telluride of the n-type in PbTe-InTe system are offered. Shown is the possibility to satisfactorily explain experimental results by filling with indium atoms In⁺² <--> In⁺¹ In⁺³ (up to 3 mol. % InTe) octahedral hollows (IH) of close-packed arrangement of tellurium atoms in PbTe crystal lattice. At the greater content of indium telluride, the allocation of both In⁺¹ on OH, and In⁺³ on tetrahedral hollows (TH), accordingly, takes place.